Analisis Penerapan Pajak Penghasilan Pasal 26 Terhadap Wajib Pajak Luar Negeri di Indonesia - Longgom Nauli Sihombing; Raihansyah Azdi Bintang; Tri Purnama Sari (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Income Tax Article 26 (PPh Article 26) is a tax instrument that regulates the taxation of income received or earned by foreign taxpayers (FTPs) from sources within Indonesia. This study aims to analyze the implementation of PPh Article 26 on foreign taxpayers in Indonesia from juridical and administrative perspectives, as well as the various challenges that arise in international taxation practices. The method used is normative legal research with a descriptive-analytical approach through a literature review of laws and regulations, academic literature, and various journals related to international taxation. The results indicate that PPh Article 26 has a strong legal basis under Law Number 36 of 2008 concerning Income Tax and is implemented through a mechanism of withholding, remittance, and reporting by domestic parties acting as tax withholders. However, its implementation still faces several challenges, including difficulties in determining taxpayer status, limited understanding of international tax regulations among taxpayers and withholding agents, administrative obstacles in utilizing Double Taxation Avoidance Agreements (DTAAs), and the potential for tax avoidance practices in cross-border transactions. To optimize the implementation of PPh Article 26, it is necessary to enhance tax socialization and education, strengthen technology-based tax administration systems, and improve international cooperation in tax information exchange.